Strategi Sukses: Memahami Pengaruh Marketing Mix 7P terhadap Perilaku Keputusan Pembelian - Benius, Benius; Raysharie, Puput Iswandyah; Irawan, Ari; Tesalonika, Donella Cleodora; Berlian, Brigita; Indriasari, Felda; Datubara, Kesia; Farida, Farida; Jaya, Michael; Sukma, Mellyana Noorlhayatie; Oktavianus, Oktavianus (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
From a conceptual standpoint, this research examines how the 7P marketing mix influences purchasing decisions. Of course, the perspective from many publications examined as well as their differences and similarities can be found in various related journals. In addition, several topics related to the impact of the 7P marketing mix on purchasing decisions will be discussed in depth and detailed in this research journal. The literature review research method is used in this research journal to gather data collected from several journals that have been combined into one journal for review and discussion in this research journal.